Profile and Role of Woman Involvement in Dry System Pig Farming - Hartoko, Hartoko (ANIMAL PRODUCTION, 2004)
This research was purposed to study the profile and role of woman involvement in dry system pig farming (pig housing with mattress from grass, pig manure, vegetable waste and kitchen waste).  The research was carried out from August to November 2003.  Pig housing areas were located on eight villages of Kertek District in Wonosobo Regency (Central Java).  The method applied was survey with intensive observation.  Sample were randomly selected, involved 180 respondents (15 percent of total pig farmers), while the locations of the sample were selected based on purposive sampling method.  The result showed that respondents were in productive age, with low formal education level. Most of all are Moslems (98%) and they have small family size.  The level of woman involvement in pig farming was high, approximately 85 percent.  They have other income source and they involve in pig farming to help their husbands in generating income.  Experience in the dry system pig farming was quite long (more than 10 years) and skill come from imitating their neighbours otherwise of autodidact. (Animal Production 6(1): 23-29 (2004) Key Words: Pig, Dry System, Woman Profile and Role